Autophagy in non-small cell lung carcinogenesis: A positive regulator of antitumor immunosurveillance - Rao, Shuan (Landes Bioscience, 2014)
In a mouse model of non-small cell lung carcinogenesis, we recently found that the inactivation of the essential autophagy gene Atg5 causes an acceleration of the early phases of oncogenesis. Thus, hyperplastic lesions and adenomas are more frequent at early stages after adenoviral delivery of Cre recombinase via inhalation, when Cre—in addition to activating the KRas(G12D) oncogene—inactivates both alleles of the Atg5 gene. The accelerated oncogenesis of autophagy-deficient tumors developing in KRas;Atg5(fl/fl) mice (as compared with autophagy-competent KRas;Atg5(fl/+) control tumors) correlates with an increased infiltration by FOXP3(+) regulatory T cells (Tregs). Depletion of such Tregs by means of specific monoclonal antibodies inhibits the accelerated oncogenesis of autophagy-deficient tumors down to the level observed in autophagy-competent controls. Subsequent analyses revealed that the combination of KRas activation and Atg5 inactivation favors the expression of ENTPD1/CD39, an ecto-ATPase that initiates the conversion of extracellular ATP, which is immunostimulatory, into adenosine, which is immunosuppressive. Pharmacological inhibition of ENTPD1 or blockade of adenosinergic receptors reduces the infiltration of KRas;Atg5(fl/fl) tumors by Tregs and reverses accelerated oncogenesis. Altogether these data favor a model according to which autophagy deficiency favors oncogenesis via changes in the tumor microenvironment that ultimately entail the Treg-mediated inhibition of anticancer immunosurveillance.